HUBUNGAN KESEGARAN JASMANI DENGAN HASIL BELAJAR PENJAS ORKES SISWA PUTRA KELAS XI SMA NEGERI 15 PEKANBARU - Muhammad Andryaldo Pradipa; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the observation that researcher did to the XI grade male students of SMAN 15 pekanbaru, ther are still many students who lack of reaching in learning achievement. The dominant deficiency is the lack of physical health in leraning and many others that unsatisfied because the less of students awareness to take care of physical fitness, so it will have an impact in the level of student learning achievement that will tent to decrease in performance. This is thought to be a contributing factor to students’ physical health. The purpose of this study is to know the relationship between studens’ phisycal fitness and learning achievement student of SMAN 15 Pekanbaru. The population of this research is all of XI Grade male students of SMAN 15 Pekanbaru that amounts to 29 students. The sample of this studt were 29 students and using total sampling technique. The instruments of this study were the primary data of respondents and secondary data in physical fitness test. The data obtained were analyzed using Product Momemt Correlation. Based on analysis normal data test X1 the result Lcount equal to 0.1327 and Ltable 0.161 while Y variable the result Lcount 0.097 Ltable 0.161. based on statistical data analysis, the data is distributed normally. Based on the test requipment of the data analysis above, the hypothesis in the variable X1 toward variable Y that 0,947 > 0,374 Rcount > Rtable data. Thus, there is a relationship between physical fitness and leraning outcomes in penjasorkes of XI grade make students of SMAN 15 pekanbaru.Key Words: physical freshness, learning outcomes